The Applicability of Artificial Intelligence in Candidate Interviews in the Recruitment Process - Anusha Hewage (The Indonesian Institute of Science and Technology Research, 2023)
This research paper examines the applicability of artificial intelligence (AI) in the recruitment and selection process, with a specific focus on the Interview phase. The study conducted qualitative interviews with 17 recruitment professionals, including hiring managers, recruiters, and HR executives, to gather their perspectives on AI adoption. The Unified Theory of Acceptance and Use of Technology (UTAUT) framework was utilized as the theoretical model to guide the research. The findings indicate that the recruitment professionals were generally receptive to using AI in various recruitment phases. However, when it came to the interview phase, there was a distinct lack of enthusiasm for AI adoption among the professionals. They expressed concerns about providing a better candidate experience and perceived AI-based interviews as a lack of commitment to candidates. As a result, regardless of the hiring volume or job group, the professionals were hesitant to integrate AI into the interview phase. The research underscores the importance of carefully selecting the appropriate recruitment stage for integrating AI and addressing the concerns raised by recruitment and selection professionals. It highlights the need to consider the candidate's experience and maintain a sense of commitment throughout the recruitment process.